Fabrication and application of hydrangea-like magnetic titanium dioxide (Fe3O4–TiO2) particles: Development of magnetic "one-step" pretreatment method for multi-pesticide residues analysis in fish. (15th June 2023) - Liu, Zhenzhen; Qi, Peipei; Zhao, Huiyu; Wang, Jiao; Wang, Zhiwei; Di, Shanshan; Xu, Hao; Wang, Qiang; Wang, Xinquan
Abstract: Magnetic titanium dioxide (Fe3 O4 –TiO2 ) was prepared and utilized as the cleanup adsorbent and separation medium to modify the QuEChERS method, affording a facile, robust, and rapid magnetic "one-step" pretreatment method for the determination of multi-pesticide residues in fish. The pretreatment key parameters, such as the dosages of the purification adsorbents (Fe3 O4 –TiO2 and PSA), the dehydrating and salting out reagents, were systematically optimized by the orthogonal test method. Under the optimal conditions, satisfactory results of method evaluation were obtained. Good linearity of 127 target analytes was obtained from 1 to 250 μg L −1 . The recoveries of 127 analytes at five spiked levels of 10, 25, 50, 125, and 250 μg kg −1 ranged from 71.0% to 129% with RSDs less than 15.0%. The method LOQs (MLOQs) of 127 analytes were 10 μg kg −1, meeting the requirement for multi-pesticide residues analysis in fish. Additionally, this magnetic "one-step" method was used for the analysis of multi-pesticide residues in real fish samples collected from Zhejiang Province, China. In summary, this method can work as a viable tool for multi-pesticide residues monitoring in fish. Graphical abstract: Image 1 Highlights: Fe3 O4 –TiO2 was prepared and employed as the cleanup adsorbent and separation medium. Magnetic "one-step" method was developed for multi-pesticide residues analysis in fish. The sample pretreatment time of this developed method was only 3 min/sample. It affords significant improvements on operation convenience and efficiency. This method gives a new approach for high-throughput sample pretreatment analysis.